Überlegungen zum Mystagogiebegriff in ausgewähltenSchriften von Karl Rahner - Celary, Ireneusz (Warszawskie Studia Teologiczne, 2019)
Presented article draws attention to the person of German theologian Karl Rahner, considerated being a „theologist of Mystery”. All Rahner’s theology has an exceptional, mistical character, but in the same way it contains the mystique which could be practised by anybody. The keystone of mystagogy proposed by German jesuit is an autenticall, original meeting between human being and God, named an transcendental experience, in which the human person enters into communication with God as a absolute Mystery. This meeting foreruns an reflexioned attitude to the experience of God, which results – on the intellectual level – with arguments of existence of God. Rahner talks about mystagogy, or mystique of ever-day reality. God is present in quotidian life of human beings as an infinity proposition, unstated love, absolute future. Real encounter with God couldn’t be limited to the practice of sacraments. It is also possible out of ecclesiastical structures – in life’s pain, in experience of hope, responsibility, love and death. First part of this article contains a short advisement about the Rahner’s definition of mistagogy. Second part of the text describes two necessary conditions of understanding Karl Rahner’s concept of mistagogy. In the third part of this work the reader can find the description of all mystagogical process by Rahner.